IMPLEMENTASI MODEL PICTURE AND PICTURE TERHADAP KEAKTIFAN SISWA PADA PEMBELAJARAN PAI KELAS 5 DI SD AL-IRSYAD TEGAL - Annisa Syahnindita Salsabila; Taukhid Mubarok (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the effectiveness of implementing the Picture and Picture model in increasing student activity in Islamic Education (PAI) learning in grade 5 of AL-IRSYAD Tegal Elementary School. The research method used is classroom action research with two cycles. The results showed that the implementation of the Picture and Picture model significantly increased student activity in PAI learning. This model facilitates interaction and discussion among students, encourages them to think critically, and creates a more lively and conducive learning atmosphere. Therefore, the Picture and Picture model is recommended for use in PAI learning and other subjects to increase student activity and participation.